Adolescents' impairment due to climate anxiety is associated with self-efficacy and behavioral engagement: a cross-sectional analysis in Quebec (Canada) - Anne-Marie Tu; Gabrielle Fortier; Richard E. Bélanger; Claude Bacque Dion; Rabi Joel Gansaonré; Scott T. Leatherdale; Slim Haddad (BMC, 2024)
Abstract Background The current understanding of climate anxiety among adolescents is sparse. This study identifies the characteristics of adolescents living in Quebec (Canada) who experience impairments induced by climate anxiety, who have feelings of self-efficacy and who adopt pro-environment behaviors. It also characterizes the association between climate anxiety, feelings of self-efficacy, and environmental actions. Methods We used a cross-sectional design to analyze data from the COMPASS study on adolescent health. Participants (n = 45 362) from 113 schools in Quebec (Canada) answered questions about climate anxiety, self-efficacy, behavioral engagement, and several indicators of well-being. Data were analyzed using ordered logistic regressions adjusted for potential confounders (age, gender, school type, material deprivation, etc.). Results 9% of adolescents reported that thinking about climate change made it difficult to sleep at least sometimes. 6% of adolescents reported that thinking about climate change interfered with their ability to get work or assignments done at least sometimes. Only 34% believed they could do something to address the problem, and 43% tried to reduce their behaviors that contribute to climate change at least sometimes. Adolescents who were boys or who were less anxious experienced less impairment and were less involved in the fight against climate change. Adolescents from less affluent families experienced more difficulty sleeping and interference with work but were not more engaged. Those with stronger school connectedness experienced less impairment and were more often involved in the fight against climate change. Adolescents who felt they could do something about climate change were more likely to try to reduce behaviors that contribute to climate change. Conclusion The findings are useful to identify and support vulnerable groups that are more likely to experience impairment due to climate anxiety. The feeling of climate self-efficacy was not well developed among some groups of adolescents. Improving adolescents' beliefs in their capacity to help address climate change may be a key strategy to promote pro-environmental actions. As the threat of climate change increases, it will be important to follow the evolution of climate anxiety and engagement among adolescents.